2017
DOI: 10.1111/pedi.12504
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes in children and adolescents is not associated with a reduced prevalence of atopy and allergic diseases

Abstract: The present cohort study shows the same prevalence of allergy and atopy in a pediatric diabetes population compared to healthy controls. Diabetes per se does not seem to influence the development of allergies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
7
1
1
Order By: Relevance
“…In contrast to previous theories, other studies have shown no differences in asthma prevalence between T1DM subjects and the general population [ 26 , 71 , 72 , 73 ]. A survey of individuals with pediatric-onset T1DM in a large German/Austrian population [ 26 ] showed that the frequency of asthma in individuals with T1DM (3,4%) was similar to the prevalence of asthma in the general population (4.7% in the German population from the German KIGGS study [ 74 ] and 5.1–7.3% in the Austrian one from the ISAAC study [ 75 ]).…”
Section: Studies Reporting No Association Between Asthma and Type 1 Diabetescontrasting
confidence: 74%
See 1 more Smart Citation
“…In contrast to previous theories, other studies have shown no differences in asthma prevalence between T1DM subjects and the general population [ 26 , 71 , 72 , 73 ]. A survey of individuals with pediatric-onset T1DM in a large German/Austrian population [ 26 ] showed that the frequency of asthma in individuals with T1DM (3,4%) was similar to the prevalence of asthma in the general population (4.7% in the German population from the German KIGGS study [ 74 ] and 5.1–7.3% in the Austrian one from the ISAAC study [ 75 ]).…”
Section: Studies Reporting No Association Between Asthma and Type 1 Diabetescontrasting
confidence: 74%
“…Jasser-Nitsche et al [ 73 ], in an Austrian survey of 104 T1DM children and 104 healthy controls, showed no differences in allergen sensitization rate and in the number of patients reporting allergy symptoms [ 73 ].…”
Section: Studies Reporting No Association Between Asthma and Type 1 Diabetesmentioning
confidence: 99%
“…A recent study conducted in Austria showed an allergen sensitization rate that was not significantly different between T1DM children and healthy controls (p = 0.625). Furthermore, a comparable number of patients in both groups reported allergic symptoms (p = 0.43) [61].…”
Section: T1d and Asthmamentioning
confidence: 81%
“…[95-97] T1DM appears to be associated with SIgAD, although individuals with T1DM have a similar prevalence of allergy and atopy when compared with the general population. [98] Compared to 0.34%the highest estimated prevalence of T1DM among the general population of Caucasians, 11 studies have found a prevalence ranging from 0% to 6.35% among SIgAD individuals, with a weighted average of 5.12%. [1,14,20,40,66,67,81,82,87,93,94] (Table 9) Two studies made use of a control population.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%